Features of the Development of Civil Society in Uzbekistan (Eurasian Research Bulletin, 2022)
This scientific article analyzes the concept of civil society, the stages of its formation and evolution. The social and legal foundations of non-governmental non-profit organizations are disclosed in the framework of reforms for the development of civil society in Uzbekistan.